Aceites lubricantes usados y parámetros orgánicos e inorgánicos del suelo en el taller de motos “PALADINES” en la ciudad de Calceta - Faubla Cusme, Bryan José (2022)
The objective of this research was to evaluate the management of used lubricating oils and the organic and inorganic parameters of the soil in the Paladines motorcycle workshop. An environmental diagnosis was made through the application of a technical sheet which delved into the activities and waste generated in said workshop, 4 activities are carried out; engine repair, oil change, electrical repairs, and engine upgrades or modifications; generating a total of 6,68 kg of solid waste and 14.201,41 ml of liquid waste, of which 10.416 were used lubricants. The organic and inorganic parameters of the soil were analyzed by sampling where 1 kg of homogeneous sample was obtained, the respective parameters were analyzed; cadmium, lead, nickel, total petroleum hydrocarbons, polycyclic aromatic hydrocarbons. The results showed that total petroleum hydrocarbons (488,55 mg/kg), polycyclic aromatic hydrocarbons (0,3 mg/kg) and cadmium (0,81 mg/kg) exceed the permissible limits, while nickel (13,80 mg/kg) and lead (10 mg/kg) are within the permissible limits stipulated by Book VI of Annex 2 of the TULSMA. A guide of good environmental practices for the management of used lubricating oils in the "Paladines" motorcycle workshop was designed, which details in an organized and objective manner the management of used lubricating oils, said guide will contribute to the proper management of oils and the respective compliance with the current environmental regulations, with the purpose of promoting the care of the soil and controlling the contamination generated in the workshop